TATA KELOLA PERTAMBANGAN MINERAL DAN BATUBARA BERDASARKAN KONSEP PASAL 33 UNDANG-UNDANG NEGARA REPUBLIK INDONESIA TAHUN 1945 - Arrum Budi Leksono, (The Juris, 2020)
The 1945 Constitution stipulates Chapter XIV Article 33 concerning "National Economy and Social Welfare" as an effort by the State through the Government to realize prosperity for all Indonesian people, which has been carefully planned by the founders of the Republic of Indonesia who are members of the Preparatory Committee to Inquire about Indonesian Independence. This study tries to examine, analyze, and find new legal theories related to the meaning of Article 33 on mineral and coal mining governance associated with Law Number 23 of 2014 concerning Regional Government. The results of the study stated that the meaning of Article 33 of the 1945 Constitution of the Republic of Indonesia related to the right to control the State which experienced a shift in authentication as stipulated in Law no. 4 of 2009 concerning Mineral and Coal Mining as amended by Law of the Republic of I Indonesia Number 3 of 2020 concerning Amendments to Law Number 4 of 2009 concerning Mineral and Coal Mining and its implementing regulations related to Law Number 23 concerning Regional Government.